Control Systems and International Institutional Instability: An Agenda for CC9 & TC 9-5. Issue 24 (2015) - Stapleton, Larry
Abstract: We live in a time of great international instability felt across major institutions including banking, political institutions and economic blocs, fed by increasingly complex technologies and socio-cultural relations. A paradigm shift is underway in which our ideas of control itself may need to change to be able to deal with the challenges humanity faces. However, the intellectual activity needed to engage in this paradigm shift remains locked into silos in the humanities, science and engineering domains. Intellectual interchange across these boundaries is not always easy, and communities often work in isolation from each other when cross-community interaction might be very important to address the challenges faced by human institutions. The IFAC CC9 Social Effects committees, and especially TC 9-5, are one of the very few groups which draw together scientists, engineers and other practitioners and experts into a multi-disciplinary forum specifically to address these challenges.